Am I too old for this, Doctor? Using population life expectancy to guide clinical decision‐making. (27th October 2016) - Broad, Joanna B; Dunstan, Kim; Claridge, Annabelle; Harris, Roger
Abstract : Objective: Prognostication is important in clinical decision‐making, especially for older people. The aim was to present estimates of life expectancy for older people in New Zealand. Methods: Statistics New Zealand age–sex‐specific death rates were used to derive quartiles of expected years of life remaining in people aged over 65 years. Results: Given current patterns and trends in New Zealand death rates, 50% of women reaching age 80 years in 2016 can expect to live at least another 10.5 years, 25% will live over 14.7 years, and 25% will die within 6.2 years. Comparable results for men reaching age 80 years in 2016 are 8.5 years, 12.7 years and 4.6 years, respectively. Of those reaching age 90 years in 2016, median expected years of life left is 4.2 years for women and 3.4 years for men. Conclusion: Demographic norms are useful as a guide when specific predictive tools are unavailable.